Evaluation of Lee–Carter model to breast cancer mortality prediction in China and Pakistan - Mubarik, Sumaira; Wang, Fang; Luo, Lisha; Hezam, Kamal; Yu, Chuanhua (Frontiers in Oncology, 2023)
Background Precise breast cancer–related mortality forecasts are required for public health program and healthcare service planning. A number of stochastic model–based approaches for predicting mortality have been developed. The trends shown by mortality data from various diseases and countries are critical to the effectiveness of these models. This study illustrates the unconventional statistical method for estimating and predicting the mortality risk between the early-onset and screen-age/late-onset breast cancer population in China and Pakistan using the Lee–Carter model. Methods Longitudinal death data for female breast cancer from 1990 to 2019 obtained from the Global Burden of Disease study database were used to compare statistical approach between early-onset (age group, 25–49 years) and screen-age/late-onset (age group, 50–84 years) population. We evaluated the model performance both within (training period, 1990–2010) and outside (test period, 2011–2019) data forecast accuracy using the different error measures and graphical analysis. Finally, using the Lee–Carter model, we predicted the general index for the time period (2011 to 2030) and derived corresponding life expectancy at birth for the female breast cancer population using life tables. Results Study findings revealed that the Lee–Carter approach to predict breast cancer mortality rate outperformed in the screen-age/late-onset compared with that in the early-onset population in terms of goodness of fit and within and outside forecast accuracy check. Moreover, the trend in forecast error was decreasing gradually in the screen-age/late-onset compared with that in the early-onset breast cancer population in China and Pakistan. Furthermore, we observed that this approach had provided almost comparable results between the early-onset and screen-age/late-onset population in forecast accuracy for more varying mortality behavior over time like in Pakistan. Both the early-onset and screen-age/late-onset populations in Pakistan were expected to have an increase in breast cancer mortality by 2030. whereas, for China, it was expected to decrease in the early-onset population. Conclusion The Lee–Carter model can be used to estimate breast cancer mortality and so to project future life expectancy at birth, especially in the screen-age/late-onset population. As a result, it is suggested that this approach may be useful and convenient for predicting cancer-related mortality even when epidemiological and demographic disease data sets are limited. According to model predictions for breast cancer mortality, improved health facilities for disease diagnosis, control, and prevention are required to reduce the disease’s future burden, particularly in less developed countries.